(untitled) (Medical Forum Monthly, 2024)
Objective: To find out the knowledge and attitude of the parents regarding the oral health of their preschool children. Study Design: Cross-sectional descriptive and analytical study Place and Duration of Study: This study was conducted at the Department of Oral Maxillofacial Surgery, Jinnah Medical and Dental College, Karachi from October to December 2016. Materials and Methods: A questionnaire based cross sectional study was conducted, the statistical population in this study was 100. The questionnaire was thoroughly explained to the parents and consent was obtained. Data were stored and analyzed using IBM-SPSS version 23.0. Independent sample t-test and One way ANOVA was done to compare the scores with occupation and number of children. Post hoc analysis was done using Tukey’s HSD test. The linear regression analysis was used to predict the scores of oral health awareness using gender and occupation of parents as independent variables. P-values less than 0.05 were considered statistically significant. Results: Results of this study showed 63% of the parents knew that the most common dental disease is tooth decay. 62% of the parents agreed that it is important to take the children for regular dental visits. 59% of the parents agreed that the nighttime bottle feeding causes dental caries. Similarly, 49% of the parents knew that eating sweets between meals cause caries. 55% of the parents believed that primary teeth caries is preventable. Toothbrush remained the most popular choice among the cleaning aid. Conclusion: It is strongly recommended to facilitate activities that help parents acquire essential education of oral health practices of their children since parents are the first role model for their children.